2015
DOI: 10.1093/protein/gzv050
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolution of affinity and stability of grafted amyloid-motif domain antibodies

Abstract: An attractive approach for designing lead antibody candidates is to mimic natural protein interactions by grafting peptide recognition motifs into the complementarity-determining regions (CDRs). We are using this approach to generate single-domain (VH) antibodies specific for amyloid-forming proteins such as the Alzheimer's Aβ peptide. Here, we use random mutagenesis and yeast surface display to improve the binding affinity of a lead VH domain grafted with Aβ residues 33-42 in CDR3. Interestingly, co-selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 75 publications
(79 reference statements)
2
43
1
Order By: Relevance
“…The antibody (V H ) domains that we isolated by co-selecting for affinity and stability17 are summarized in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibody (V H ) domains that we isolated by co-selecting for affinity and stability17 are summarized in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently observed strong affinity/stability trade-offs during the directed evolution of a human antibody (V H ) domain specific for the Alzheimer’s Aβ42 peptide17. We generated mutant libraries of a stable V H antibody scaffold (B1a18) that was initially grafted with Aβ residues 33–42 in CDR3, displayed the mutants on the surface of yeast, and selected for V H domains with improved binding affinity.…”
mentioning
confidence: 99%
“…bility, we first analyzed the relative affinity of the A␤17-42 domains for Protein A. This analysis is motivated by the fact that folded V H 3 domains (such as the A␤17-42 domains) have a Protein A binding site on their scaffold, and the relative binding of Protein A to V H 3 domains is correlated with V H stability (45,48,49). Using an ELISA assay to measure V H binding to immobilized Protein A, we found that the NNN, QQQ, and SSS variants had similar IC 50 values of ϳ1-2 nM, whereas the DDD and EEE variants had higher IC 50 values (ϳ5-10 nM; Fig.…”
Section: Polar Cdr3 Mutations Strongly Impact Expression Levels Of A␤mentioning
confidence: 99%
“…However, it is more challenging to select sets of rare mutations that improve binding but are not destabilizing. The importance of simultaneously optimizing affinity and stability was recently demonstrated in selections of yeast-displayed gammabodies where simultaneous selection for antigen binding and Protein A binding was employed [121]. …”
Section: Introductionmentioning
confidence: 99%